2014
DOI: 10.1213/ane.0000000000000199
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Girth, Vertebral Column Length, and Spread of Spinal Anesthesia in 30 Minutes after Plain Bupivacaine 5 mg/mL

Abstract: Multiple regression analysis revealed that the combination of a patient's 5 general characteristics, especially abdominal girth and vertebral column length, had a high predictive value for the spread of spinal anesthesia after a given dose of plain bupivacaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 17 publications
6
39
1
Order By: Relevance
“…As the VCL increases the spread of hyperbaric bupivacaine is limited to lower dermatome levels. Although these two previous studies were conducted with parturient patient population, in the current study we found similar correlation results in non pregnant patient population between VCL and the spread of spinal anaesthesia which is in accordance with the results of Zhou et al (9).…”
Section: Discussionsupporting
confidence: 93%
“…As the VCL increases the spread of hyperbaric bupivacaine is limited to lower dermatome levels. Although these two previous studies were conducted with parturient patient population, in the current study we found similar correlation results in non pregnant patient population between VCL and the spread of spinal anaesthesia which is in accordance with the results of Zhou et al (9).…”
Section: Discussionsupporting
confidence: 93%
“…A high correlation between both abdominal girth and vertebral column length and lumbosacral cerebrospinal fluid volume was the primary finding of this study, which further explains the results of our previous studies . In our studies, we have demonstrated that abdominal girth and dorso‐sacral distance have a high predictive value for the spinal spread after a given dose of plain bupivacaine and can largely predict a suitable dose of plain bupivacaine for lower limb surgery.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, the adjusted R 2 (0.644) for the regression equation between abdominal girth, dorso‐sacral distance and lumbosacral cerebrospinal fluid volume was lower than the adjusted R 2 for the regression equation between abdominal girth, vertebral column length and spinal spread in our previous study . This might be because that in current study the three‐dimensional volume of the lumbosacral cerebrospinal fluid was not the true sense of lumbosacral cerebrospinal fluid.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Chun et al (10) also found that IAP did not correlate with SAD. Although most of the studies have assessed abdominal obesity by measuring the abdominal girth in parturients (6,(12)(13)(14), Katulanda et al (15) suggested that the distance between the lower border of the xiphisternum and the center of the umbilicus could be used as an anthropometric measure to define abdominal obesity. Therefore, we decided to include the SPX as well as the SPF in our study.…”
Section: Discussionmentioning
confidence: 99%